Laboratory Intercomparison of Pleistocene Bone Radiocarbon Dating Protocols. Issue 5 (21st June 2017) - Huels, Matthias; van der Plicht, Johannes; Brock, Fiona; Matzerath, Simon; Chivall, David
Abstract: Since its invention in the late 1940s, radiocarbon ( 14 C) dating has become an important tool for absolute dating. A prerequisite for the acceptance of this method is consistency between, and compatibility of, 14 C dates from different laboratories. To meet these requirements, international laboratory intercomparison studies with different sample materials are frequently performed (e.g. TIRI, FIRI, VIRI and, most recently, SIRI).Intercomparison is especially relevant and difficult for samples close to the dating limit of 50 kBP, not least for bone samples. A 14 C intercomparison study between the Leibniz-Laboratory in Kiel (Germany), the Center for Isotope Research (CIO) in Groningen (the Netherlands), and the Oxford Radiocarbon Accelerator Unit (ORAU, United Kingdom) was performed on three Pleistocene (MIS3) mammal bone samples from the Brick Quarry site Coenen (BQC) in Germany. The comparison of individually prepared and measured bone collagen 14 C activities, results from shared collagen measurements, and respective background signatures and correction points to the latter as the main factor responsible for observed differences in final given radiocarbon estimates.